Joint Optimization of the Trajectory and the Main Parameters of an Electric Propulsion System. (2017) - Petukhov, V.G.; Wook, Woo Sang
Abstract: The problem of joint optimization of the trajectory of a spacecraft with an electric propulsion system and for the main parameters of electric propulsion and power supply systems is considered. It is well known that for every space transportation operation there is an optimal value of specific impulse of electric propulsion corresponding to the minimum total mass of the system, the power supply system ensuring electric propulsion operation, and the propellant. It is easy to show that there is also an optimal value of electric power of an electric propulsion system, associated with the growth of the required characteristic velocity with the thrust decrease. Optimal specific impulse and electric power can be found only by joint optimization of the trajectory and design parameters of electric propulsion. A simple spacecraft mass budget model and the maximum principle are used for optimization. The necessary optimality conditions for the specific impulse and electric power of electric propulsion system are derived. Numerical examples of the joint optimization of interplanetary trajectory, electric power and specific impulse of electric propulsion systems are presented.